MENINGKATKAN PEREKONOMIAN PEMBUATAN POTATO BALL MELALUI UMKM DI KELURAHAN GAJAHMUNGKUR - Kurniawati, Endang; Wahyuningsih, Susanti; Fauziyah, Ika Rahmawati; Riskina, Fika; Sa’adah, Lailatus; Rohana, Ida; Ariana, Fitri Suci (STIE Pelita Nusantara, 2025)
In Indonesia, although potatoes have high nutritional value and can be used as an important food source, there are still several reasons why people are not very interested in them. One of the main problems is the lack of knowledge about the benefits of potatoes and innovative and varied ways to cook them. Many Indonesians still eat rice as a source of carbohydrates, so potatoes are not considered a healthy alternative. The level of acceptance of potatoes in Indonesia is influenced by taste preferences and culinary culture in addition to these factors. Potatoes are often considered unfamiliar or not in accordance with local tastes because Indonesian people tend to prioritize traditional foods such as rice and noodles. Efforts are needed to change this perception by promoting potatoes as a versatile food ingredient that can be included in various traditional Indonesian dishes with modifications that suit local tastes. Therefore, we took the initiative to change the public's view of potatoes from just an ordinary food ingredient to a source of inspiration for creating creative and nutritious dishes called